2013
DOI: 10.1007/s13277-013-0675-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil selectively enriches stem-like cells in the lung adenocarcinoma cell line SPC

Abstract: Most adult stem cells are in the G0 or quiescent phase of the cell cycle and account for only a small percentage of the cells in the tissue. Thus, isolation of stem cells from tissues for further study represents a major challenge. This study sought to enrich cancer stem cells and explore cancer stem-like cell clones using 5-fluorouracil (5-FU) in the lung adenocarcinoma cell line, SPC. Proliferation inhibition was analyzed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assays, according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Indeed, Shi et al observed that 5-FU selected a population of cells with increased SP pheno-type and that the isolated SP 1 cells possessed increased clone-forming ability and invasiveness in vitro and increased tumourigenicity. 72 This same approach has already been successfully used in other types of cancer. For instance, in 2010 Ma and colleagues selected sphere cells from a human ovarian cancer cell line using cisplatin and paclitaxel.…”
Section: Therapy-enrichment Of Lung Cancer Stem-like Cellsmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, Shi et al observed that 5-FU selected a population of cells with increased SP pheno-type and that the isolated SP 1 cells possessed increased clone-forming ability and invasiveness in vitro and increased tumourigenicity. 72 This same approach has already been successfully used in other types of cancer. For instance, in 2010 Ma and colleagues selected sphere cells from a human ovarian cancer cell line using cisplatin and paclitaxel.…”
Section: Therapy-enrichment Of Lung Cancer Stem-like Cellsmentioning
confidence: 94%
“…Indeed, Shi et al . observed that 5‐FU selected a population of cells with increased SP phenotype and that the isolated SP + cells possessed increased clone‐forming ability and invasiveness in vitro and increased tumourigenicity . Moreover, several authors have reported an increase in the number of tumour cells expressing cancer stem‐like markers, such as CD133, ALDH1A1, ABCG2, Nanog, Oct3/4 or Notch upon treatment of patients with anticancer therapy.…”
Section: Therapy‐enrichment Of Lung Cancer Stem‐like Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their existence could help to explain the clinical observation of the inaction of conventional cancer chemotherapy and radiotherapy in some instances since these treatments target rapidly dividing cells yet stem cells by nature are slow-cycling. For example, treatment with fluorouracil (5-FU) selects and enriches the cancer stem cell population since the rapidly dividing cells would be killed while slow-cycling ones incorporate the drug at a lower rate ( Shi et al., 2013 , Wang et al., 2006 ). Potentially, therapies targeting cancer stem cells could be more effective ( Duggal et al., 2014 ).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…It has been suggested that prolonged exposure of cisplatin resulted in stem cell like characters including decreased proliferation, accumulation of resistant cells in G0/G1 phase of cell cycle, enhanced colony formation ability, higher ALDH activity, increased frequency of CD133 and CD44 positive cells and higher expression of Oct4/ Sox2/ Nanog and EMT markers like C-Met and β-catenin (Barr et al, 2013). Exposure to 5-FU was also found to enrich stem-like cancer cells in lung adenocarcinoma cells (Shi et al, 2013). Resistance against DNA damaging agents was tested by examining the alteration of DNA-damage repair proteins in stem-like cells from a panel of NSCLC cell lines (Lundholm et al, 2013).…”
Section: Molecular Targeting Of Lung Cancer Stem Cellsmentioning
confidence: 99%